Razvoj moderne intenzivne medicine u Republici Srpskoj (region Banja Luke) - Kovačević, Peđa (Scripta Medica, 2023)
Critical care medicine as relatively young discipline, started developing in mid-1950s in response to epidemy of poliomyelitis. This branch of medicine evolved much faster in high-income countries (HIC) than in low resource settings (LRS) where the Republic of Srpska (Western Balkan) belongs. The experience of setting up a modern critical care program under the LRS constraints as a promising way forward to meet the increased demand for critical care worldwide is described. Main tool was systematic analysis of written documents related to the establishment of the first multidisciplinary MICU and its development to the present day. Successful development is contingent on formal education and continued mentorship from HIC, establishment of a multidisciplinary team, the support from local health care authorities, development of a formal subspecialty training, academic faculty development and research. Critical care medicine is a critical public health need in HIC and LRS alike.
Keywords: Intenzivna medicina; Zemlje sa niskim ili srednjim prihodima; Razvoj